Structural Behavior of Prestressed Concrete Bridge Girder with Epoxy Joint - Assylkhan Jalairov; Dauren Kumar; Khaini-Kamal Kassymkanova; Zeynep Sarsembekova; Gulzhan Nuruldaeva; Gulnar Jangulova (Communications - Scientific letters of the University of Zilina, 2022)
The study object is a prototype of a composite bridge prestressed concrete beam with a length of 42.0 m for road bridge desks for perception of impact from motor vehicles in the form of A14, NK-120 and NK-180 loads.The experimental deflection of the beam in the midspan had a value equal to fexp = 62.4 mm at a load of 2Pк = 436 kN, which was 75.2% of the control deflection value.Based on the test results, the girder block joints with "tooth" and "notch" device are found to be imperfect.The experimental load of 2PMAX = 822.7 kN was achieved during the tests, which exceeded the control load equal to 2Pк = 744 kN when checking the strength of the composite beam and the control load equal to 2Pк = 790 kN when checking the strength of No. 1 and No. 2 joints.